Effects of simulated highway noise on heart rates of larval monarch butterflies, Danaus plexippus: implications for roadside habitat suitability - Davis, Andrew K. (Biol Lett, 2018)
Developed countries around the world are criss-crossed with vast networks of roadways. Conservationists have recently focused attention on roadsides as possible locations for establishing pollinator habitat, with the monarch butterfly (Danaus plexippus) featuring prominently in such discussions. However, roadsides are inherently loud, which could negatively affect developing larvae. We conducted a series of experiments testing if simulated highway noise stresses monarch larvae, which we gauged by non-destructive monitoring of heart rates. In two replicated experiments, larvae exposed for 2 h experienced a significant increase in heart rate (16 and 17% elevation), indicating they perceive traffic noise as a stressor. Meanwhile, experiments exposing larvae for either 7 or 12 days to continuous traffic noise both showed no heart rate elevation at the end of larval development, suggesting chronic noise exposure leads to habituation or desensitization. Habituation to stress as larvae may impair reactions to real-world stressors as adults, which could be problematic for a butterfly that undertakes an annual two-month migration that is fraught with dangers. More generally, these results could have far-reaching implications for the billions of insects worldwide that develop near roadways, and argue that further study is needed before promoting roadside habitat for butterfly conservation.